KETERAMPILAN SISWA KELAS VIII SMP NEGERI 1 O’O’U DALAM MEMBACAKAN TEKS BERITA - Firman Duho (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The background to the problem of this research is that students in reading news texts have not shown results that meet the minimum completeness criteria. This is evident from the average score of students which only reaches 60, while the minimum completion criteria for Indonesian language subjects reaches 75. This research aims to determine the clarity of articulation, accuracy of intonation, fluency, volume of voice, suitability of facial expressions when reading news texts for class VIII students. O'o'u State Middle School 1. The approach used in this research is a descriptive approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this research are that there are still students who are poor at reading news texts because they lack mastery of several aspects, including unclear pronunciation, lack of confidence, and students still use a low volume of voice and lack confidence in reading it. Students still look shy and hesitant when reading news texts in front of the class. Apart from that, students also do not pay attention to the punctuation marks in the news text. Suggestions for future researchers, the results of this research can be used as material for further research on the principles of politeness in Indonesian.